Local variations of the piezoelectric properties of an LiNb(1−x)TaxO3 crystal. Issue 2 (1st April 2023) - Gureva, Polina; Kulikov, Anton; Mololkin, Anatoli; Fakhrtdinov, Rashid; Artemev, Alex; Demkiv, Andrey; Pisarevsky, Yury; Marchenkov, Nikita
Abstract : Because of the significant difference in the piezoelectric moduli between lithium niobate and lithium tantalate, variation of the piezoelectric properties in local regions of the crystal can appear. A correlation between the change in the piezoelectric properties and the composition in a mixed lithium niobate–tantalate crystal was established. Abstract : An in situ study of the spatial distribution of the piezoelectric properties of an LiNb(1− x ) Ta x O3 crystal (⟨ x ⟩ = 0.088) in an external DC electric field was performed by the method of X‐ray diffraction of synchrotron radiation at angles close to 180°. The variation of the d 22 piezoelectric coefficient was determined with high accuracy (up to 2%) in local areas by the angular shift of the diffraction maximum under the action of the electric field ( E = 1582 V mm −1 ) applied on the crystal along the Y axis, during scanning along the X and Z directions. A correlation between the piezoelectric strain amplitude and the concentration of tantalum obtained by X‐ray fluorescence mapping has been established.